HUMAN MILK AND HUMAN MILK BANKS: ADVANCES, CHALLENGES, AND INNOVATIONS IN NEONATAL FOOD CONSERVATION AND SAFETY - Machado, Deborah Heloise Fernandes; Vignoto, Maria Fernanda Miriani; da Silva, Lorena Maia; Bombonato, Lorena Moran; dos Santos, Anne Caroline Boreski; Bolognese, Marciele Alves; Buranello, Catharina Paula; Alexandre, Vinicius (Editora Impacto Científico, 2025)
Human milk is recognized as the gold standard of neonatal nutrition, especially for premature newborns, due to its nutritional composition and numerous bioactive components with immunological, anti-inflammatory, and metabolic functions. In this context, Human Milk Banks (HMBs) play a fundamental role in promoting, protecting, and supporting breastfeeding, as well as in the collection, processing, quality control, and safe distribution of donated human milk. This study consists of a narrative literature review aiming to analyze the composition and benefits of human milk, the importance of breastfeeding in premature infants, the role of HMBs, and the conservation methods used, with an emphasis on emerging technologies such as lyophilization. The search was conducted in the PubMed, SciELO, and Google Scholar databases, including articles published between 1980 and 2024. The analyzed studies show that, although Holder pasteurization is effective in ensuring microbiological safety, it can partially compromise heat-sensitive components of human milk. In this scenario, lyophilization emerges as a promising alternative, capable of extending the stability, shelf life, and preservation of the bioactive properties of human milk, as well as facilitating storage and distribution. It is concluded that human milk banks remain essential pillars of neonatal public health and that investment in technological innovation, combined with scientific research, is strategic for optimizing the conservation and utilization of donated human milk. DOI: https://doi.org/10.56238/edimpacto2025.077-001